Assessing the Teaching of Writing : Twenty-First Century Trends and Technologies - Dayton, Amy E. (Book collections on Project MUSE., 2015)
Although fraught with politics and other perils, teacher evaluation can contribute in important, positive ways to faculty development at both the individual and the departmental levels. Yet the logistics of creating a valid assessment are complicated. Inconsistent methods, rater bias, and overreliance on student evaluation forms have proven problematic. The essays in Assessing the Teaching of Writing demonstrate constructive ways of evaluating teacher performance, taking into consideration the immense number of variables involved. Contributors to the volume examine a range of fundamental issue.